E-017 Cerebrovascular Decision Making: Professional and Personal Preferences. (26th July 2014) - Tanweer, O; Wilson, T; Kalhorn, S; Golfinos, J; Huang, P; Kondziolka, D
Abstract : Introduction: It is known that physicians sometimes recommend treatment that, in a similar clinical scenario, they might not choose for themselves. We sought to understand this dynamic across cerebrovascular practice and examine how neurosurgeons value the procedures they offer. Methods: We conducted an online survey sent to a large cohort of neurosurgeons in May 2013. Respondents were randomised to answer either as the surgeon or as the patient. The questions involved patients presenting with 1) an epidural hematoma (control), 2) un-ruptured anterior communicating artery aneurysm, 3) incidentally found right temporal AVM, 4) spontaneous intracranial and intraventricular haemorrhage in deep structure. Data on practice parameters and experience levels was also collected. Results: We obtained 534 survey responses, 279 responding as the "neurosurgeon", and 255 as the "patient, " with a response rate of 19.7%. Demographics amongst the two groups of survey takers was similar. There was no difference in the management of an epidural hematoma, as expected. For the unruptured aneurysm, the rates of opting for treatment was similar amongst respondees. However within the treatment group there was a trend for survey takers to more often chose coiling for themselves and clipping for patients (p = 0.056). Surgeons, however, with a greater than 30% open-cerebrovascular practice had less of a tendency to do so. For arteriovenous malformation management, there was no statistical difference between choosing treatment or conservative management. However, amongst the respondees who chose treatment, more respondees chose resection/embolization for their patient but radiosurgery for self (p = 0.001). In a case of a large spontaneous intracranial and intraventricular haemorrhage neurosurgeons were more likely to place a ventricular drain in a patient than himself or herself. Neurosurgeons in practice more than 10 years since residency were more likely to recommend against interventions for aneurysms, AVMs or intracranial haemorrhage. Conclusions: In the majority of cases altering the role of the surgeon did not change the decision to pursue treatment or conservative treatment. In certain clinical scenarios, however, neurosurgeons choose treatment options for themselves that are different than what they would choose for their patients. For the management of an arteriovenous malformations, intracranial aneurysms, and hypertensive haemorrhage, responses favored less invasive interventions when the surgeon was the patient. These findings are likely a result of cognitive biases, previous training, experience, areas of expertise, and personal values. Disclosures: O. Tanweer: None. T. Wilson: None. S. Kalhorn: None. J. Golfinos: None. P. Huang: None. D. Kondziolka: None.